Managers in Polish Organizations - the Results of Empirical Research - Wnuk, Izabela Bednarska (European Journal of Economics and Business Studies, 2016)
Today we are dealing with unceasing changes that are not without influence on the functioning of the organization and its subsystems; and managers, who are specific moderators of all activities in the organization, in the face of the volatility of the environment, need to acquire new competences and roles, and realize relevant functions. It seems that the manager’s role may be dependent on organizational characteristics such as the type of organization (for-profit, non-profit), the industry in which the organization operates and its size. These features can determine the roles and functions of the persons responsible for the management of organizations. Taking this into account, the aim of this article is to present the role of managers in Polish organizations, depending on their industry and size based on the results of empirical research. The study was conducted in 2015 among 289 organizations in Poland. One of their objectives was to identify a modern role of managers, depending on the selected organizational features based on interviews with people responsible for personnel policy in these organizations. Studies have shown that the role of the manager and basically just its scope is dependent on the size of the organization. On the other hand, no relationship between the role and the industry in which the organization operates has been observed.